Astragalus polysaccharide: implication for intestinal barrier, anti-inflammation, and animal production - Liang, Hui; Tao, Siming; Wang, Yanya; Zhao, Jing; Yan, Chang; Wu, Yingjie; Liu, Ning; Qin, Yinghe (Frontiers in Nutrition, 2024)
Intestine is responsible for nutrients absorption and plays a key role in defending against various dietary allergens, antigens, toxins, and pathogens. Accumulating evidence reported a critical role of intestine in maintaining animal and human health. Since the use of antibiotics as growth promoters in animal feed has been restricted in many countries, alternatives to antibiotics have been globally investigated, and polysaccharides are considered as environmentally friendly and promising alternatives to improve intestinal health, which has become a research hotspot due to its antibiotic substitution effect. Astragalus polysaccharide (APS), a biological macromolecule, is extracted from astragalus and has been reported to exhibit complex biological activities involved in intestinal barrier integrity maintenance, intestinal microbiota regulation, short-chain fatty acids (SCFAs) production, and immune response regulation, which are critical for intestine health. The biological activity of APS is related to its chemical structure. In this review, we outlined the source and structure of APS, highlighted recent findings on the regulation of APS on physical barrier, biochemical barrier, immunological barrier, and immune response as well as the latest progress of APS as an antibiotic substitute in animal production. We hope this review could provide scientific basis and new insights for the application of APS in nutrition, clinical medicine and health by understanding particular effects of APS on intestine health, anti-inflammation and animal production.